A Systematic Literature Review of Cultured Meat Through the Conceptual Frameworks of the Entrepreneurial Ecosystem and Global Value Chain - Chiara Benussi; Antonella Samoggia (Foods)
Cultured meat (CM) is currently experiencing a surge in popularity, primarily due to its promise to produce animal-based products with a lower environmental impact and a higher level of animal welfare. Although CM production remains limited and lacks pre-market approval (except for Singapore and the USA), recent technological advancements have been notable. A greater number of stakeholders, including biotechnology companies, start-ups, private investors, NGOs and big agrifood companies, are entering the CM value chain. This paper aims to aggregate, synthesize, and analyze existing studies on the CM value chain to highlight the characteristics, methodologies, and topics they address. Our secondary purpose is to analyze elements emerging in terms of global value chain dynamics. To do so, this study applies a conceptual framework based on the interplay of the Entrepreneurial Ecosystem and global value chain frameworks. This systematic literature review identifies 43 studies and shows that the most addressed topics are regulations on pre-market approval and labelling, technological progress, the use of patents, the availability and sources of funding, and actors’ roles in the CM market. The analysis and discussion of these findings highlight key aspects of the CM global value chain and present further areas of research to investigate the governance of the chain.